Asesmen Kinerja Sistem Pembangkit Solar Fotovoltaik Terintegrasi Jala Jala 3 Fasa - Arafi Adi Mussalam; Tindyo Prasetyo (Journal of Creative Student Research, 2026)
This study aims to analyze the performance of a three-phase grid-connected solar photovoltaic (PV) power system with a capacity of 8.72 kWp installed at MA Darul Ihsan Muhammadiyah, Sragen, Central Java, Indonesia. The system comprises 16 monocrystalline modules (545 Wp each, configured in 2 strings × 8 series) connected to a 10 kW Sungrow string inverter. Data were collected over one month (April) using a quantitative-experimental method, covering solar irradiance, module temperature, DC input power, AC output power, system efficiency, daily energy production, and load sharing between the PV system and the PLN utility grid. Results show a peak irradiance of 730 W/m², a maximum output power of 6,050 W, and a mean system efficiency of 94.32%. Total energy production in April reached 1,096.5 kWh (average 36.55 kWh/day), with a Performance Ratio (PR) of 83.22%, classified as good performance under IEC 61724. Load sharing analysis indicates that the PV system contributed 22.28% while the utility grid supplied 77.72% of the total building consumption of 4,920.5 kWh. This study confirms that grid-connected PV integration in educational facilities is technically viable and capable of reducing grid energy consumption by approximately one-fifth of total building energy demand.